2015
DOI: 10.1159/000441077
|View full text |Cite
|
Sign up to set email alerts
|

In vitro<b> </b>Autoradiographic Analysis of Regional Changes in Estrogen Receptor Alpha in the Brains of Cycling Female Rats

Abstract: Background/Aims: The contributions of the three principal ovarian steroid hormones (estradiol, progesterone and testosterone) to the regulation of estrogen receptor alpha (ERα) levels in the rat brain were examined during the estrous cycle. Methods: Receptor concentrations were measured using an in vitro autoradiographic technique designed to separately quantify free, unoccupied receptors and receptors ‘occupied' by (bound to) endogenous hormone. Results: ERα occupation increased at proestrus and declined at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Mice have approximately a four-day cycle where estradiol and progesterone peak across proestrus, driving sexual motivation during estrous, and return to low levels during metestrus and diestrus 37 . Across the estrous cycle, changes in estrogen receptors themselves have been documented in areas of the hypothalamus 38,39 . Importantly, it has been shown that even in this short time span, structural and functional plasticity occurs within these motivational circuits [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…Mice have approximately a four-day cycle where estradiol and progesterone peak across proestrus, driving sexual motivation during estrous, and return to low levels during metestrus and diestrus 37 . Across the estrous cycle, changes in estrogen receptors themselves have been documented in areas of the hypothalamus 38,39 . Importantly, it has been shown that even in this short time span, structural and functional plasticity occurs within these motivational circuits [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%